APLICACION TAXONOMICA DE UN METODO ESTADISTICO - VARGAS, LUIS (My University, 1942)
Facing the problem of Anopheles species identification the author applies a statistical method susceptible of use in other biological laboratories working on taxonomy He points out the advantages and inconveniences of the method and presents illustration
REV INST SALUBR ENFERM TROP
Keywords: APLICACION, TAXONOMICA, METODO, ESTADISTICO; CIENCIAS MEDICAS